The Relationships and Differences of the Kantian Philosophy and Pedagogy in Regard to Postmodern Pedagogic - Zieliński, Paweł (Wydawnictwo Naukowe UAM, 2018)
The aim of the study is articulated in the title. The author is reconstructing Kantian philosophy and pedagogic, the thesis of postmodernism and post-modern pedagogic and indicates the relationships and differences of those two systems. Both Kant and the Baden-based neo-Kantians enabled the emancipation of the humanities. The Kantian model of pedagogy was the basis for pedagogic directions, belonging to the meta-theory of humanistic education and critical pedagogy, especially the postmodern one. There are clear links with Kantian ideas of pedagogy, the way to capture the role of dignity, knowledge and freedom in the morality of a human being. There are also significant differences: Kant did not include to his pedagogy social, political and pluralistic questions, which are so important in postmodern pedagogy.
Podobieństwa i różnice pomiędzy filozofią i pedagogiką Kanta a pedagogiką ponowoczesną
Keywords: Kantian philosophy and pedagogy; postmodern pedagogy; moral education; identity of the person; humanistic pedagogy